Iron-rich colloids as carriers of phosphorus in streams: A field-flow fractionation study. (1st August 2016) - Baken, Stijn; Regelink, Inge C.; Comans, Rob N.J.; Smolders, Erik; Koopmans, Gerwin F.
Abstract: Colloidal phosphorus (P) may represent an important fraction of the P in natural waters, but these colloids remain poorly characterized. In this work, we demonstrate the applicability of asymmetric flow field-flow fractionation (AF4) coupled to high resolution ICP-MS for the characterization of low concentrations of P-bearing colloids. Colloids from five streams draining catchments with contrasting properties were characterized by AF4-ICP-MS and by membrane filtration. All streams contain free humic substances (2–3 nm) and Fe-bearing colloids (3–1200 nm). Two soft water streams contain primary Fe oxyhydroxide-humic nanoparticles (3–6 nm) and aggregates thereof (up to 150 nm). In contrast, three harder water streams contain larger aggregates (40–1200 nm) which consist of diverse associations between Fe oxyhydroxides, humic substances, clay minerals, and possibly ferric phosphate minerals. Despite the diversity of colloids encountered in these contrasting streams, P is in most of the samples predominantly associated with Fe-bearing colloids (mostly Fe oxyhydroxides) at molar P:Fe ratios between 0.02 and 1.5. The molar P:Fe ratio of the waters explains the partitioning of P between colloids and truly dissolved species. Waters with a high P:Fe ratio predominantly contain truly dissolved species because the Fe-rich colloids are saturated with P, whereas waters with a low P:Fe ratio mostly contain colloidal P species. Overall, AF4-ICP-MS is a suitable technique to characterize the diverse P-binding colloids in natural waters. Such colloids may increase the mobility or decrease the bioavailability of P, and they therefore need to be considered when addressing the transport and environmental effects of P in catchments. Graphical abstract: Highlights: We measured colloidal P species in streamwater by AF4 coupled to ICP-MS. Different streams contain a variety of highly diverse colloids. Small colloids (3–5 nm) dominate in soft waters; harder waters contain colloids >20 nm. P is predominantly bound by Fe-rich colloids.